Health-related concepts and cognitive linguistics - Raguž, Marija, etnologinja (Array, 2020)
Human behavior is governed by concepts. Concepts are cognitive representations of reality. Cognitive linguistics suggests that there are cognitive models affecting the formation of concepts in human mind, such as cognitive metaphor and a prototype model. We used the example of an ancient procedure – trepanation in order to show the connection between the procedure and the concept of the skull as a container, which is a metaphor. Most important concepts in medical systems are health and disease. There is no agreement about their exact definition, although there have been many studies focusing on that. Based on the previous research, we suggest possible benefits from approaching the disease as a prototype category. In all studies so far there have always been consistencies in rating entities qualifying as a disease which is a feature of a prototype category – membership gradience. Entities perceived as diseases by respondents in studies so far have not been the same, but they share certain features. It is more likely for an entity to be considered a disease if it can lead to death, for example. In our opinion there are common core features determining disease as a cognitive category. Further cross-cultural studies could answer what features an entity needs to have in order to be considered a disease.Stressing such features could improve patients’cooperation when a new disease appears.